2012
DOI: 10.1152/ajprenal.00634.2011
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2EP3 receptor regulates cyclooxygenase-2 expression in the kidney

Abstract: Cyclooxygenase-2 (COX-2) is constitutively expressed and highly regulated in the thick ascending limb (TAL). As COX-2 inhibitors (Coxibs) increase COX-2 expression, we tested the hypothesis that a negative feedback mechanism involving PGE(2) EP3 receptors regulates COX-2 expression in the TAL. Sprague-Dawley rats were treated with a Coxib [celecoxib (20 mg·kg(-1)·day(-1)) or rofecoxib (10 mg·kg(-1)·day(-1))], with or without sulprostone (20 μg·kg(-1)·day(-1)). Sulprostone was given using two protocols, namely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…We hypothesize that COX-2 is under tonic suppression by a negative feedback mechanism involving EP 3 receptors, as COX-2-dependent PGE 2 synthesis by the mTAL after exposure to HS was potentiated when EP 3 receptors were inhibited. As EP 3 receptor-dependent feedback inhibition in the TAL was also observed in response to treatment with COX-2-selective inhibitors (37), the present study suggests that PGE 2 signaling via EP 3 receptors in the TAL may be part of a mechanism that regulates mTAL COX-2 expression and function in response to diverse stimuli. Since PGE 2 inhibits Na ϩ -K ϩ -Cl Ϫ cotransporter 2 activity (22), this mechanism may be teleologically important to prevent excessive loss of NaCl and/or the regulation of urinary concentrating mechanisms due to the prodigious ability of the TAL to reabsorb NaCl.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…We hypothesize that COX-2 is under tonic suppression by a negative feedback mechanism involving EP 3 receptors, as COX-2-dependent PGE 2 synthesis by the mTAL after exposure to HS was potentiated when EP 3 receptors were inhibited. As EP 3 receptor-dependent feedback inhibition in the TAL was also observed in response to treatment with COX-2-selective inhibitors (37), the present study suggests that PGE 2 signaling via EP 3 receptors in the TAL may be part of a mechanism that regulates mTAL COX-2 expression and function in response to diverse stimuli. Since PGE 2 inhibits Na ϩ -K ϩ -Cl Ϫ cotransporter 2 activity (22), this mechanism may be teleologically important to prevent excessive loss of NaCl and/or the regulation of urinary concentrating mechanisms due to the prodigious ability of the TAL to reabsorb NaCl.…”
Section: Discussionsupporting
confidence: 62%
“…We (37) have also previously found that administration of the EP 3 receptor agonist sulprostone decreased the number of cells expressing COX-2. Upregulation of EP 3 receptors in response to HS intake is consistent with data showing that administration of a high-salt diet (4% NaCl) to rats increased EP 3 receptor mRNA levels (20) and may be part of a mechanism that regulates the COX-2/PGE 2 signaling pathway.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations